Role of ICT Initiatives in Sustainable Progress of Rural Women in India - Soundari, M. Hilaria (European Journal of Sustainable Development, 2016)
Abstract The lower status, lost dignity, and denied rights of women across the rural India comes out with a clarion call to promote sustainable progress in their lives. Information and Communication Technology (ICT) has emerged as one of a dynamic tool in their lives. It has been successful in connecting the rural and remote population to the wider world. These tools are initiated for gender equality and women’s sustainable progress. Its success largely depends on the availability and accessibility for the rural women. The main objectives of the study was to present the successful elements of ICT initiatives in the significant process of sustainable development, to trace out the barriers and bottlenecks of ICT initiatives in rural India and to identify the areas of further strengthening the effectiveness of ICT initiatives in sustainable progress of rural women. Of the four sample ICT initiatives, two of the initiatives were situated in southern India i.e. Karnataka and Tamil Nadu and the other two were in the northern part of India i.e. Gujarat and Rajasthan. The study also identified the requirement for basic education, technical skills, tailored training for women and above all engendering of ICT policies. Women are one of the wonderful creations and co-creators of the universe. However, the history of human civilization testified to the changing status of women all through the history. In 19th and 20th centuries, reform movements led by great social reformers provided better avenues to women’s legal status. Nevertheless, independent India continued to witness upheavals against women oppression despite its Constitution providing equality.